The Implementation of the Electronic Village Administrative System (Sedulur) to Support the Realization of Cirebon as a Smart City - Safitri, Amelia; Rahmadina, Cindy Aulia; Siswoyo, Mukarto (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the implementation of the Electronic Village Administrative System (SEDULUR) as part of the Cirebon City Government’s e-government initiative to enhance efficiency, accessibility, and transparency in public services. Using a qualitative approach and Agarwal’s five-stage e-government theory—website existence, interaction, collaboration, technical complexity, and information-push—the study finds that SEDULUR is still at the initial stage of website existence. Limitations include unidirectional functionality, minimal system sophistication, and restricted access limited to village-level operators, primarily due to the revocation of regional authority. While the system has assisted operators in service delivery, it has not yet reached its full potential. The study recommends further development of SEDULUR to meet all stages of e-government maturity, enabling more effective services and encouraging greater public participation.